The Role of Emotions in Consumer Brand Loyalty: A Neuromarketing Approach - Shukla, Priyanshu; Awasthi, Apoorv; Kumari, Sakshi; Sahil, Sahil; Gandh, Nityanadi Kumar; Agustin, Fina Erviana; Nneoma, Nwodo Rita (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
In today's competitive marketplace, cultivating and maintaining consumer brand loyalty is a paramount objective for businesses. While traditional marketing research has explored various factors influencing brand loyalty, the role of emotions, often overlooked in the past, has gained prominence in recent years. This research delves into the intricate relationship between emotions and consumer brand loyalty, employing a cutting-edge neuromarketing approach to uncover the subconscious processes at play. By utilizing neuroimaging techniques, such as functional magnetic resonance imaging (fMRI) and electroencephalography (EEG), this study seeks to unveil the neural mechanisms that underlie emotional responses to brands. Through carefully designed experiments and data analysis, the research aims to identify specific emotional triggers that elicit brand loyalty and evaluate the neurological basis of these responses. Furthermore, this investigation will explore how various emotional states, including joy, trust, and nostalgia, influence different aspects of brand loyalty, such as repeat purchases, positive word-of-mouth, and resistance to competitive alternatives. By pinpointing the neurological signatures of emotional brand attachment, marketers can develop more precise and effective strategies to foster and strengthen consumer brand loyalty. The findings of this research hold significant implications for marketing practitioners.